We are given that f(x)=(x-1)^2 and g(x)=x^1/2. Now, to deterrmine the value for gof(x) we first have to find f(x) and substitute the result we get as the x value in g(x).

Now we know that f(x) = (x-1)^2

Also, g(x) = x^1/2

So g(f(x)) = g( (x-1)^2)

= [(x-1)^2)]^(1/2)

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We are given that f(x)=(x-1)^2 and g(x)=x^1/2. Now, to deterrmine the value for gof(x) we first have to find f(x) and substitute the result we get as the x value in g(x).

Now we know that f(x) = (x-1)^2

Also, g(x) = x^1/2

So g(f(x)) = g( (x-1)^2)

= [(x-1)^2)]^(1/2)

=(x-1)^(2/2)

=(x-1)

**Therefore g(f(x)) = gof(x) = (x-1)**